Method for preparing high-iron-content microcrystalline glass by utilizing regenerated copper smelting slag

By crushing, grinding and screening the regenerated copper smelting slag, combined with high temperature melting and heat treatment of fly ash, boric acid and quicklime, high iron-containing microcrystalline glass is prepared, which solves the problems of high energy consumption, high pollution and low absorption in the prior art regenerated copper smelting slag, and achieves efficient and low-cost resource utilization.

CN119569342APending Publication Date: 2025-03-07CHINA ENERGY CONSERVATION ENG TECH RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411743623.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When dealing with recycled copper smelting slag, the prior art consumes high energy, is highly polluted, and the copper slag consumption is low, making it difficult to achieve efficient recycling and resource utilization.

Method used

The copper smelting slag is regenerated by crushing, grinding and screening, and mechanically inclusion copper particles are removed, and mixed with materials such as fly ash, boric acid and quicklime, and undergo high-temperature melting and heat treatment to prepare high-iron microcrystalline glass.

Benefits of technology

This method shortens industrial processes, saves energy, increases product added value, and realizes low-cost and high-value utilization of recycled copper smelting slag, solving environmental pollution problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005163073410000011
    Figure HDA0005163073410000011
  • Figure HDA0005163073410000012
    Figure HDA0005163073410000012
Patent Text Reader

Abstract

The invention provides a method for preparing high-iron-content glass ceramics by utilizing regenerated copper smelting slag, which comprises the following steps: step 1, pretreating the regenerated copper smelting slag, including crushing, grinding and screening, so as to remove mechanically mixed copper; 2, the pretreated regenerated copper smelting slag is mixed with fly ash, boric acid and quick lime, and a mixture is obtained; 3, the mixture is subjected to high-temperature melting, and a molten mass is formed; step 4, carrying out annealing treatment on the molten mass to form base glass; and 5, carrying out nucleation and crystallization heat treatment on the base glass to form the microcrystalline glass. Through specific pretreatment and melting processes, the environmental problems of the regenerated copper smelting slag and the fly ash are solved, and the microcrystalline glass with relatively high hardness and bending strength is prepared and can be used as a building and industrial material. In addition, the preparation method provided by the invention also has the characteristics of low cost, high benefit and no pollution, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing high-iron-content microcrystalline glass by utilizing recycled copper smelting slag, and belongs to the technical field of solid waste recycling. Background Art

[0002] Copper-containing solid wastes such as waste circuit boards, electroplating sludge and copper smelting soot have the characteristics of large social reserves, rich element types and high metal content. Their green and efficient recycling can produce significant economic and environmental benefits. In industry, pyrometallurgy has become the mainstream process for recycled copper smelting due to its advantages such as strong raw material adaptability, large processing volume and high recovery rate. However, a large amount of slag will be produced after high-temperature smelting. These recycled copper smelting slags contain copper, iron and other toxic heavy metals. Their disposal and resource utilization are one of the current problems in the industry.

[0003] At present, common methods for disposing recycled copper smelting slag include landfill, reduction roasting and cement solidification. Among them, although the landfill method is low in cost, it not only occupies a large amount of land, but also easily causes soil and groundwater pollution. Reduction roasting is to separate and recover heavy metals such as iron and copper through carbon thermal reduction or other reduction methods, and reduce the pollution properties of copper slag. For example, China's invention patent (CN117660751A) discloses a resource-based method for aluminum ash slag to synergistically treat copper slag. The specific principle is to use the main component AlN in aluminum ash slag to react easily with water to generate ammonia. Ammonia has strong reducing properties and can replace copper in copper slag under high-temperature roasting conditions to achieve the recycling of copper slag. For another example, China's invention patent (CN115504676A) discloses a technology for treating copper slag using carbon thermal reduction, mixing copper slag, calcium chloride and steel slag in a certain proportion and then roasting, spraying carbon into the roasted slag, and separating metal from slag after carbon thermal reduction. Although the above reduction roasting method can effectively recover copper from recycled copper smelting slag, the copper content in these copper slags is low, so the recovery benefit is small. In addition, whether aluminum ash slag or carbon is used as a reducing agent, a large amount of harmful gases will be generated. The cement solidification method uses copper slag to produce cement, but due to its low activity, poor hydrophilicity and high iron content in the slag, the cement and concrete produced have poor performance and low absorption capacity, which cannot fundamentally solve the problem.

[0004] Although there are attempts to produce glass by melting copper slag, such as the Chinese invention patent (CN 113845308A) that discloses a method for preparing microcrystalline glass by using copper slag and converter slag, the method uses copper slag to add high-temperature molten converter slag to reduce and recover iron, and then mixes and melts the discharged tailings and zinc-containing dust to obtain basic glass, and finally obtains microcrystalline glass through a heat treatment process. Although this method successfully produces microcrystalline glass, it requires the separation of iron by reduction smelting, which consumes a lot of energy and releases a large amount of CO. 2 .

[0005] In view of this, it is necessary to design a method for directly preparing high-iron-content microcrystalline glass using copper slag to solve the above problems. Summary of the invention

[0006] The present invention aims to provide a method for preparing high-iron-content microcrystalline glass from recycled copper smelting slag, so as to solve the problems of high energy consumption, high pollution and low copper slag consumption in the prior art. Compared with the traditional reduction roasting treatment process, the present invention shortens the industrial process, saves energy and increases the added value of the product.

[0007] To achieve the above object, the present invention adopts the following technical solution: a method for preparing high-iron-containing microcrystalline glass from recycled copper smelting slag, comprising the following steps:

[0008] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material;

[0009] Step 2: Mix the powder raw material with fly ash, boric acid and quicklime in a set ratio to obtain a mixture;

[0010] Step 3: Melting the mixture at 1300-1500° C. for 0.5-2 hours to form a melt;

[0011] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass;

[0012] Step 5: Keep the base glass at 600-750°C for 0.5-2.5h to complete nucleation, and keep it at 800-950°C for 0.5-2.5h to complete crystallization to obtain microcrystalline glass.

[0013] Preferably, as an improvement, the raw material of the regenerated copper smelting slag in step 1 comprises one or more of waste circuit boards, electroplating sludge, copper smelting soot, and waste copper, and the chemical composition of the regenerated copper smelting slag comprises: FeO mass fraction of 15-30%, SiO 2 The mass fraction is 15-32%, the mass fraction of CaO is 6-18%, and the mass fraction of Al 2 O 3 The mass fraction is 8 to 25%, and the remainder is impurities.

[0014] Preferably, as an improvement, the composition weight parts of the mixture in step 2 are: 40-60 parts of recycled copper smelting slag, 30-40 parts of fly ash, 5-10 parts of boric acid, and 5-10 parts of quicklime, with a total of 100 parts.

[0015] Preferably, as an improvement, in the mixed material obtained by mixing the recycled copper smelting slag, fly ash, boric acid and quicklime in step 2, the FeO mass fraction is 10-20%, and the SiO mass fraction is 10-20%. 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0016] The technical principles of this solution are as follows:

[0017] (1) The inventors have found that the content of chemically dissolved copper in recycled copper smelting slag is about 0.4-0.6%, which has almost no effect on the preparation of microcrystalline glass. However, mechanically included copper particles will significantly inhibit the phase separation process of the melt, thereby reducing the mechanical properties of the microcrystalline glass. The present application scheme utilizes the good ductility of copper and removes the mechanically included copper in the recycled copper smelting slag through a combination of crushing, grinding and screening, thereby greatly reducing the adverse effects of copper particles on the mechanical properties of microcrystalline glass.

[0018] (2) The iron content in recycled copper smelting slag is high and often exists in the form of ferrous oxide. The corresponding glass formers such as SiO 2 The content of fly ash is too low, resulting in insufficient precipitation of glass phase. The inventor combined fly ash with SiO 2 、Al 2 O 3 , Fe 2 O 3 , CaO and TiO 2 The characteristics of SiO 2 and Al 2 O 3 The content of SiO accounts for more than 70% of the total 2 With Al 2 O 3 can be glass network formers and glass network intermediates, respectively, to form a basic glass phase; B provided by boric acid 2 O 3It not only acts as a glass network intermediate to promote the formation of the basic glass phase, but also utilizes the high BO bond strength and stable coordination structure to allow B in the slag to gradually replace Al and Si, forming a layered BO three-coordinate or four-coordinate structure, ultimately reducing the viscous resistance of the melt, improving fluidity, and achieving glass melting clarification.

[0019] (3) The inventors added an appropriate amount of CaO to provide a nucleating agent and increase the oxidizability of the slag, which is beneficial for converting FeO into a glass network intermediate Fe 2 O 3 . It also uses Fe 2 O 3 As a nucleating agent for microcrystalline glass, it promotes crystal precipitation.

[0020] Beneficial effects of this program:

[0021] 1) The method adopted by the present invention separates the copper mechanically included in the recycled copper smelting slag through simple crushing, grinding and screening operations, thereby reducing energy consumption;

[0022] 2) The method adopted by the present invention is based on the composition characteristics of the recycled copper smelting slag, and the SiO 2 and Al 2 O 3 , B in boric acid 2 O 3 Provide the basic structural units that make up the glass network and meet the composition requirements of basic glass;

[0023] 3) The quicklime added in the method adopted by the present invention can not only serve as a flux, but also promote the conversion of FeO into Fe 2 O 3 , which is beneficial to lower the melting temperature and promote nucleation and crystallization;

[0024] 4) The method adopted in the present invention uses recycled copper smelting slag and fly ash as raw materials to directly prepare high-iron-content microcrystalline glass, which not only solves the environmental problems of recycled copper smelting slag and fly ash, but also the obtained microcrystalline glass has high hardness and bending strength, realizing low-cost and high-value utilization of solid waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the X-ray diffraction pattern of the glass-ceramics of Example 1 of the present invention;

[0026] Figure 2 This is a microstructure diagram of the microcrystalline glass according to Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product instructions are used.

[0028] In the description of the present invention, unless otherwise specified, the terms "upper" and "lower" and the like indicate positions or state relationships based on the positions or state relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0029] In the following examples, the instruments and equipment used without indicating the manufacturer are all conventional products that can be purchased through regular channels. The methods described are conventional methods unless otherwise specified, and the raw materials described can be obtained from public commercial channels unless otherwise specified.

[0030] Embodiment 1:

[0031] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag, comprising the following steps:

[0032] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material, namely, recycled copper smelting slag powder.

[0033] Step 2: 50 parts of powder raw materials, 30 parts of fly ash, 10 parts of boric acid, and 10 parts of quicklime are mixed, and the parts mentioned in this application are parts by weight to obtain a mixture, and each component in the mixture meets the following requirements (if there is a specific content of each component, it can be written here to better correspond to the following technical effects. If not, it can also be described in a general way as it is now, that is, the components in the mixture meet the requirements of the content of each component): FeO mass fraction is 10-20%, SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0034] Step 3: The mixed material is melted at a high temperature of 1500° C. for 1 hour to form a melt.

[0035] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0036] Step 5: Keep the base glass at a nucleation temperature of 650°C for 1.5 hours to complete nucleation, keep it at 850°C for 1.5 hours to complete crystallization, and cool it to obtain microcrystalline glass. The test results of microcrystalline glass are detailed in Figure 1 and Figure 2 .

[0037] The hardness and flexural strength of the prepared microcrystalline glass are respectively 692.22 HV and 121.34 MPa in Vickers hardness, and 99.12% and 99.75% in acid and alkali resistance.

[0038] Embodiment 2:

[0039] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag. The main method is similar to that of Embodiment 1, except for the selection of specific parameters, and includes the following steps:

[0040] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material.

[0041] Step 2: Mix 40 parts of powder raw materials, 40 parts of fly ash, 10 parts of boric acid, and 10 parts of quicklime to obtain a mixture, wherein the mass fraction of FeO in the mixture is 10-20%, and the mass fraction of SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0042] Step 3: The mixed material is melted at a high temperature of 1300° C. for 2 hours to form a melt.

[0043] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0044] Step 5: Keep the base glass at a nucleation temperature of 600°C for 1 hour to complete nucleation, keep it at 800°C for 1 hour to complete crystallization, and cool it to obtain microcrystalline glass.

[0045] The hardness and flexural strength of the prepared microcrystalline glass are respectively 667.16 HV and 111.52 MPa in Vickers hardness, and 98.97% and 99.07% in acid and alkali resistance.

[0046] Embodiment 3:

[0047] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag. The main method is similar to that of Embodiment 1, except for the selection of specific parameters, and includes the following steps:

[0048] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material.

[0049] Step 2: Mix 60 parts of powder raw materials, 30 parts of fly ash, 5 parts of boric acid, and 5 parts of quicklime to obtain a mixture, wherein the mass fraction of FeO in the mixture is 10-20%, and the mass fraction of SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0050] Step 3: The mixed material is melted at a high temperature of 1300° C. for 1.5 hours to form a melt.

[0051] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0052] Step 5: Keep the base glass at a nucleation temperature of 750°C for 2.5 hours to complete nucleation, keep it at 950°C for 2.5 hours to complete crystallization, and cool it to obtain microcrystalline glass.

[0053] The hardness and flexural strength of the prepared microcrystalline glass are respectively 732.48 HV and 129.63 MPa in Vickers hardness, and 99.06% and 99.45% in acid and alkali resistance.

[0054] Embodiment 4:

[0055] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag. The main method is similar to that of Embodiment 1, except for the selection of specific parameters, and includes the following steps:

[0056] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material.

[0057] Step 2: Mix 55 parts of powder raw materials, 30 parts of fly ash, 5 parts of boric acid, and 10 parts of quicklime to obtain a mixture, wherein the mass fraction of FeO in the mixture is 10-20%, and the mass fraction of SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0058] Step 3: The mixed material is melted at a high temperature of 1400° C. for 2 hours to form a melt.

[0059] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0060] Step 5: Keep the base glass at a nucleation temperature of 600°C for 2 hours to complete nucleation, keep it at 850°C for 1.5 hours to complete crystallization, and cool it to obtain microcrystalline glass.

[0061] The hardness and flexural strength of the prepared microcrystalline glass are respectively 709.26 HV and 119.47 MPa, and the acid and alkali resistance are respectively 98.99% and 99.36%.

[0062] Embodiment 5:

[0063] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag. The main method is similar to that of Embodiment 1, except for the selection of specific parameters, and includes the following steps:

[0064] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material.

[0065] Step 2: Mix 50 parts of powder raw materials, 35 parts of fly ash, 5 parts of boric acid, and 10 parts of quicklime to obtain a mixture, wherein the mass fraction of FeO in the mixture is 10-20%, and the mass fraction of SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0066] Step 3: The mixed material is melted at a high temperature of 1350° C. for 1.5 hours to form a melt.

[0067] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0068] Step 5: Keep the base glass at a nucleation temperature of 700°C for 1 hour to complete nucleation, keep it at 800°C for 0.5 hour to complete crystallization, and cool it to obtain microcrystalline glass.

[0069] The hardness and flexural strength of the prepared microcrystalline glass are respectively 722.14 HV and 125.36 MPa in Vickers hardness, and 99.73% and 99.26% in acid and alkali resistance.

[0070] Embodiment 6:

[0071] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag. The main method is similar to that of Embodiment 1, except for the selection of specific parameters, and includes the following steps:

[0072] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material.

[0073] Step 2: Mix 50 parts of powder raw materials, 40 parts of fly ash, 5 parts of boric acid, and 5 parts of quicklime to obtain a mixture, wherein the mass fraction of FeO in the mixture is 10-20%, and the mass fraction of SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0074] Step 3: The mixed material is melted at a high temperature of 1450° C. for 0.5 h to form a melt.

[0075] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0076] Step 5: Keep the base glass at a nucleation temperature of 700°C for 2 hours to complete nucleation, keep it at 900°C for 1 hour to complete crystallization, and cool it to obtain microcrystalline glass.

[0077] The hardness and flexural strength of the prepared microcrystalline glass are respectively 725.91 HV and 127.04 MPa in Vickers hardness, and 99.21% and 99.59% in acid and alkali resistance.

[0078] Embodiment 7:

[0079] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag. The main method is similar to that of Embodiment 1, except for the selection of specific parameters, and includes the following steps:

[0080] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material.

[0081] Step 2: Mix 45 parts of powder raw materials, 40 parts of fly ash, 10 parts of boric acid, and 5 parts of quicklime to obtain a mixture, wherein the mass fraction of FeO in the mixture is 10-20%, and the mass fraction of SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0082] Step 3: The mixed material is melted at a high temperature of 1500° C. for 0.5 h to form a melt.

[0083] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0084] Step 5: Keep the base glass at a nucleation temperature of 750°C for 1.5 hours to complete nucleation, keep it at 800°C for 2.5 hours to complete crystallization, and cool it to obtain microcrystalline glass.

[0085] The hardness and flexural strength of the prepared microcrystalline glass are respectively 730.21 HV and 118.42 MPa in Vickers hardness, and 99.17% and 98.89% in acid and alkali resistance.

[0086] Embodiment 8:

[0087] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag. The main method is similar to that of Embodiment 1, except for the selection of specific parameters, and includes the following steps:

[0088] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material.

[0089] Step 2: Mix 50 parts of powder raw materials, 35 parts of fly ash, 5 parts of boric acid, and 10 parts of quicklime to obtain a mixture, wherein the mass fraction of FeO in the mixture is 10-20%, and the mass fraction of SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0090] Step 3: The mixed material is melted at a high temperature of 1350° C. for 2 hours to form a melt.

[0091] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0092] Step 5: Keep the base glass at a nucleation temperature of 700°C for 2.5 hours to complete nucleation, keep it at 850°C for 1.5 hours to complete crystallization, and cool it to obtain microcrystalline glass.

[0093] The hardness and flexural strength of the prepared microcrystalline glass are respectively 707.91 HV and 115.96 MPa in Vickers hardness, and 99.37% and 99.19% in acid and alkali resistance.

[0094] Embodiment 9:

[0095] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag. The main method is similar to that of Embodiment 1, except for the selection of specific parameters, and includes the following steps:

[0096] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material.

[0097] Step 2: Mix 45 parts of powder raw materials, 35 parts of fly ash, 10 parts of boric acid, and 10 parts of quicklime to obtain a mixture, wherein the mass fraction of FeO in the mixture is 10-20%, and the mass fraction of SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0098] Step 3: The mixed material is melted at a high temperature of 1500° C. for 1 hour to form a melt.

[0099] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0100] Step 5: Keep the base glass at a nucleation temperature of 750°C for 1.5 hours to complete nucleation, keep it at 950°C for 1 hour to complete crystallization, and cool it to obtain microcrystalline glass.

[0101] The hardness and flexural strength of the prepared microcrystalline glass are respectively 715.48 HV and 125.25 MPa in Vickers hardness, and 99.26% and 98.86% in acid and alkali resistance.

[0102] Embodiment 10:

[0103] This embodiment provides a method for preparing high-iron-containing glass-ceramics using recycled copper smelting slag. The main method is similar to that of Embodiment 1, except for the selection of specific parameters, and includes the following steps:

[0104] Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material.

[0105] Step 2: Mix 50 parts of powder raw materials, 35 parts of fly ash, 10 parts of boric acid, and 5 parts of quicklime to obtain a mixture, wherein the mass fraction of FeO in the mixture is 10-20%, and the mass fraction of SiO 2 The mass fraction is 22-32%, Al 2 O 3 The mass fraction is 10-16%, the mass fraction of CaO is 20-30%, and the mass fraction of B 2 O 3 The mass fraction is 3-6%, the mass fraction of MgO is 0.5-3%, and the mass fraction of K 2 O mass fraction is 0~2%, Na 2 O mass fraction is 0~2%, TiO 2 The mass fraction is 0~1%.

[0106] Step 3: The mixed material is melted at a high temperature of 1450° C. for 1.5 hours to form a melt.

[0107] Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass.

[0108] Step 5: Keep the base glass at a nucleation temperature of 650°C for 2 hours to complete nucleation, keep it at 900°C for 1.5 hours to complete crystallization, and cool it to obtain microcrystalline glass.

[0109] The hardness and flexural strength of the prepared microcrystalline glass are respectively 719.26 HV and 137.18 MPa in Vickers hardness, and 99.41% and 99.09% in acid and alkali resistance.

[0110] The above is only an embodiment of the present invention, and the common sense such as the known specific structure, characteristics and reactant ratio in the scheme is not described too much here. It should be pointed out that for those skilled in the art, without departing from the concept of the present invention, some deformations and improvements can also be made, such as simply adjusting the selection of parameters within or near the specified parameter range, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The protection scope required by this application shall be based on the content of its claims, and the specific implementation methods in the specification and other records can be used to explain the content of the claims.

Claims

1. A method for preparing high-iron glass-ceramics from recycled copper smelting slag, characterized in that: The specific steps include: Step 1: crush and grind the recycled copper smelting slag, and pass it through a 300-mesh sieve to obtain a uniformly dispersed powder raw material; Step 2: Mix the powder raw material with fly ash, boric acid and quicklime in a set ratio to obtain a mixture; Step 3: Melting the mixture at 1300-1500° C. for 0.5-2 hours to form a melt; Step 4: preheat the mold at 650°C, take out the mold and pour the melt into it, keep the mold at 600°C for 0.5h and cool it with the furnace to obtain the basic glass; Step 5: Keep the base glass at 600-750°C for 0.5-2.5h to complete nucleation, and then keep it at 800-950°C for 0.5-2.5h to complete crystallization to obtain microcrystalline glass.

2. The method for preparing high-iron glass-ceramics from recycled copper smelting slag according to claim 1, characterized in that: The raw materials for regenerating copper smelting slag in step 1 include one or more of waste circuit boards, electroplating sludge, copper smelting ash, and waste copper.

3. The method for preparing high-iron glass-ceramics from recycled copper smelting slag according to claim 1, characterized in that: The chemical composition of the regenerated copper smelting slag in step 1 includes: FeO mass fraction of 15-30%, SiO2 mass fraction of 15-32%, CaO mass fraction of 6-18%, Al2O3 mass fraction of 8-25%, and the remainder is impurities.

4. The method for preparing high-iron glass-ceramics from recycled copper smelting slag according to claim 1, characterized in that: The components of the mixture in step 2 are as follows by weight: 40-60 parts of recycled copper smelting slag, 30-40 parts of fly ash, 5-10 parts of boric acid, and 5-10 parts of quicklime, with a total of 100 parts.

5. The method for preparing high-iron-containing glass-ceramics from recycled copper smelting slag according to claim 1, characterized in that: The mixed material obtained in step 2 includes: FeO with a mass fraction of 10-20%, SiO2 with a mass fraction of 22-32%, Al2O3 with a mass fraction of 10-16%, CaO with a mass fraction of 20-30%, B2O3 with a mass fraction of 3-6%, MgO with a mass fraction of 0.5-3%, K2O with a mass fraction of 0-2%, Na2O with a mass fraction of 0-2%, and TiO2 with a mass fraction of 0-1%.

Citation Information

Patent Citations

  • Preparation method of low-cost glass ceramic

    CN113845308A

  • Method for valuable metal extraction and high-value utilization of residues in copper slag

    CN115504676A

  • Recycling method for co-processing copper slag through aluminum ash and slag

    CN117660751A